REDESIGN OF MSME TAX POLICY IN INDONESIA: CHALLENGES AND EFFORTS TO IMPROVE TAX COMPLIANCE - Rio Nugraha Pratama; Andries Lionardo; Katriza Imania; Raniasa Putra (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This article aims to identify the factors causing the resistance of MSME taxpayers to transition from fulfilling tax obligations based on turnover to fulfilling tax obligations based on net profit, which requires bookkeeping, and then formulate solutions to these problems. The problem is focused on the causes of MSME taxpayers' resistance to using bookkeeping. To approach this problem, the theoretical reference from Robert B. Seidman and Nalin Abeysekere is used, namely the Rule, Opportunity, Capacity, Communication, Interest, Process, and Ideology (ROCCIPI) method. Data were collected through literature studies and interviews with MSME taxpayers and tax officials, which were then analyzed qualitatively. This study concludes that additional actions from the tax authorities are needed to change taxpayer behavior so that they are interested in maintaining bookkeeping and calculating their taxes in accordance with general tax provisions. These incentives can be in the form of special additional tariff adjustments for MSMEs, the provision of integrated bookkeeping support facilities, continuous assistance and socialization, and improving the government's image in building trust and awareness among taxpayers.